The Causes and Mitigation Measures of Fall from Height Accident in Malaysia - Muhammad Fikri Hasmori; Mohamad Arif Mat Salleh; Noratira Abd Samad (International Journal of Sustainable Construction Engineering and Technology, 2022)
Falls from height (FFH) is a significant threat to the construction environment and are the leading cause of serious and fatal injuries for construction workers. Working at a height increases the likelihood of being involved in a fall from a height accident. Since the construction industry is carried out in risky environments, it is experiencing accidents at different severity rates, some causing minor injuries, some causing severe injuries, and some resulting in fatalities. Most fall from height accidents will affect the individual, such as permanent disabilities, worker fatalities, and affect the psychology of workers. This research objective is to find the cause and effect of fall from height accidents and mitigation measures in Malaysia. The findings of this research indicate that individual attitude is the main contributing factor to falls from height accidents, with the top five highest Relative Important Index (RII) ranking. The main causes of fall from height accidents are individual attitudes, which is workers' negligence toward safety rules with RII=0.901. Then, the respondent strongly agrees that the humanitarian categories of injuries or permanent disabilities with RII=0.899 are the adverse effects of fall from height accidents. After that, the utmost possible mitigation measures with the highest RII ranking are in the health protection categories, which forbid working at height if alcohol or drugs have been detected on workers with RII=0.930. Lastly, the identified causes of FFH accidents were selected to be used in the Loughborough ConAC Model. The establishment of the model is important to clearly represent the FFH accident and ultimately to reduce the fall from height accidents in Malaysia.